Analyzing the existing value chains of fruits and vegetables in selected upazilas of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2023)
Reducing postharvest losses of fruits and vegetables is a major pathway to food and nutrition security in Bangladesh. A survey was conducted in 30 selected upazilas of Bangladesh from February to October 2021 to explore the nature and magnitude of postharvest losses. This study assessed the knowledge gap, attitudes and practices of the value chain’s key actors, and the status of market opportunities in the country. A total of 515 farmers and 295 traders were interviewed from selected upazilas of the country. The findings of this study revealed that 50-70% of growers showed a positive attitude toward good agriculture practices (GAP), maturity indices, and the role of good packaging in keeping the products safe for consumers. More than 41% of farmers aggregated their harvested commodities beside the field on direct soil contact under open sunlight. Only 27% of farmers and traders washed fruits and vegetables before marketing, of which 32% used unsafe water found in the canal or ditches. On average, 86.91% of farmers and traders sorted out their products before marketing for a better price. More than 56% of farmers and traders used jute or nylon sac for packaging fresh fruit and vegetables. Nevertheless, only 20.2% of farmers and 24.41% of traders used plastic crates as packaging containers. Generally, the farmer used different local vehicles, including three-wheeler van, rickshaw, bi-cycle, tempo, etc. In contrast, the traders transported their produce to the wholesale market using a truck and pick-up van. The average postharvest losses were estimated 12.5% at the farm level, whereas 6.7% at trader’s level up to the wholesale market.Int. J. Agril. Res. Innov. Tech. 13(1): 123-130, June 2023